Topological properties of generalized Wallman spaces and lattice relations - James A. Allan (International Journal of Mathematics and Mathematical Sciences)
Let X be an abstract set and ℒ be a lattice of subsets of X. Associated with the pair (X,ℒ) are a variety of Wallman-type topological spaces. Some of these spaces generalize very important topological spaces such as the Stone-Čech compactification, the real compactification, etc. We consider the general setting and investigate how the properties of ℒ reflect over to the general Wallman Spaces and conversely. Completeness properties of the lattices in the Wallman Spaces are investigated, as well as the interplay of topological properties of these spaces such as T2, regularity and Lindelöf with ℒ.